2002
DOI: 10.1089/10799900260475759
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γInduction by SCG, 1,3-β-D-Glucan fromSparassis crispa, in DBA/2 MiceIn Vitro

Abstract: Sparassis crispa Fr. in an edible mushroom recently cultivable in Japan. A branched beta-glucan from S. crispa (SCG) is a major 6-branched 1,3-beta-D-glucan showing antitumor activity. In this study, we examined interferon-gamma (IFN-gamma) induction by SCG from splenocytes in DBA/2 mice in vitro. In the splenocytes derived from almost all inbred strains of mice except for DBA/1 and DBA/2 mice, IFN-gamma production was not induced by SCG. The breeder and genders of DBA/2 mice showed no influence on IFN-gamma i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 52 publications
2
63
0
3
Order By: Relevance
“…Recently, we found that GM-CSF is a key molecule for cytokine induction by β-glucan, and that GM-CSF production is specifically induced in DBA/2 mice in vitro (12,14,15). In this study, we investigated the key factors in the cytokine induction by SCG in CY-treated mice, and found that GM-CSF plays an important role in this system.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Recently, we found that GM-CSF is a key molecule for cytokine induction by β-glucan, and that GM-CSF production is specifically induced in DBA/2 mice in vitro (12,14,15). In this study, we investigated the key factors in the cytokine induction by SCG in CY-treated mice, and found that GM-CSF plays an important role in this system.…”
Section: Discussionmentioning
confidence: 93%
“…Splenocytes were prepared as previously described (12). Briefly, the spleen was teased apart in RPMI 1640 medium, and after centrifugation, the single-cell suspension was treated with ACK-lysing buffer (8.29 g/liter NH 4 Cl, 1 g/liter KHCO 3 , 37.2 mg/liter EDTA/ 2Na) to lyse the red blood cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported that both serum IgE levels and the scratching amount of NC/Nga mice that were induced dermatitis by a continuous application of hapten are reduced by oral administration of S. crispa (Hasegawa et al, 2004). Furthermore, a branched beta-glucan from S. crispa can induce IFN-γ in DBA/2 mice (Harada et al, 2002). However, the effects of oral administration of S. crispa on Th1/Th2 balance and allergic rhinitis have not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%